Navigating Aging: Battling Illness, Overcoming Disabilities, Embracing Dependency, and Confronting Discrimination (SMC Journal of Sociology, 2025)
This paper investigates the challenges faced by aging people, focusing on the critical issues, like illness, disability, dependency, poverty and social discrimination. As elderly population continues to grow due to improved healthcare and life expectancy, the complexities of their daily lives become more pronounced. There are numerous factors that result in illness, disability, dependency, poverty, and discrimination. We need a holistic approach to address intersecting factors that shape and reshape each other in aging. This study explores how cultural norms, economic factors, healthcare accessibility, family dynamics influence the experience of aging individuals. It examines the ways in which traditional respect for the elderly is being reshaped by modern pressures, such as urbanization, modernization and migration. The article also delves into the socio-economic conditions that exacerbate health problems and disabilities, emphasizing the role of inadequate pension systems and social security. Additionally, it focuses on how social discrimination and isolation impacts on physical and mental well-being in the elderly. Through the combination of qualitative and quantitative data and narratives, this paper provides a comprehensive understanding of the multifaceted challenges faced  by aging individuals. It also calls for more inclusive and aging friendly policies and support systems to improve the quality of life for the aging individuals.